A casa do Minho - Uma reflexão sobre o habitar - Francisco Areias Moreira de Sá (2017)
This work, presented under the title "A Casa do Minho", will be established in a consolidated area in Vila Nova de Cerveira, Gondarém. The master dissertation will be the synthesis of personal and critical reflection on a set of fundamental themes related to the topic of single-family housing/dwelling. Topics of interest will be addressed, not only for the architecture course, but also for daily living. In this way, this dissertation will have the possibility to realize a real project, with real clients, for a vacation home and weekends. A first reading of the place, made up of approximations, back and forward, will seek to analyze the area in study and what defines it, so that, between "reality and drawing", part of these readings are formed, in project. The purpose of this work will be to produce a proposal for single family housing, which will stimulate a reflection on the theme dwelling. It will highlight some themes that, through the hypotheses formulated during the design process and the comparison with other architectural works, will serve as a basis to base the reflection. The questioning of these concepts will serve to justify the seized project decisions in the development of the project. Summarizing, the dissertation will be developed through the program, framework and analysis; description of design processes; questioning of themes and concepts, and finally, the reasoned presentation of the final project. Effectively the thesis focuses on the design and reflections are around the theme that conects it, single-family housing.